Foliar application of rare earth elements on soybean (Glycine max (L)): Effects on biometrics and characterization of phytotoxicity - Rodrigues, Eduardo S.; Montanha, Gabriel S.; Marques, João P.R.; de Almeida, Eduardo; Yabuki, Lauren N.M. [UNESP]; Menegário, Amauri A. [UNESP]; Pereira de Carvalho, Hudson W. (Elsevier, 2020)
This study aims at investigating the effects of foliar application of aqueous solutions of La3+ and Ce3+ nitrates on soybean plants (Glycine max). First, we observe that Triton HW 1000 surfactant at 0.01 vol% reduces droplets contact angle and increases their drying time. Under greenhouse conditions, the foliar treatments do not affect chlorophyll content, plant height, number of leaves, number of pods, number of seeds per pod, and average seed weight. However, the treatments induce phytotoxicity since foliar injuries appear after the spraying. Microprobe X-ray fluorescence spectroscopy combined to scanning electron microscopy shows that the leaf lesions are positively correlated to accumulation of Ce and La on the leaf surface and also promote structural alteration to the epidermal cells. X-ray absorption near edge structure shows that the La and Ce nitrates are partially bio transformed into oxides by the leaves which might explain the harmful effects.
Keywords: Leaf fertilization; Rare earth elements; Soybean; X-ray absorption spectroscopy; X-ray fluorescence spectroscopy